Mathematics Questions and Answers – Logarithmic Differentiation

«
»

This set of Mathematics Multiple Choice Questions & Answers (MCQs) focuses on “Logarithmic Differentiation”.

1. Differentiate (log⁡2x)sin⁡3x with respect to x.
a) (3 cos⁡3x log⁡(log⁡2x)+\(\frac{sin⁡3x}{x log⁡2x}\))
b) \(log⁡2x^{sin⁡3x} \,(3 \,cos⁡3x \,log⁡(log⁡2x)+\frac{sin⁡3x}{x \,log⁡2x})\)
c) –\((3 \,cos⁡3x \,log⁡(log⁡2x)+\frac{sin⁡3x}{x log⁡2x})\)
d) \(\frac{3 \,cos⁡3x \,log⁡(log⁡2x)+\frac{sin⁡3x}{x log⁡2x}}{log⁡2x^{sin⁡3x}}\)
View Answer

Answer: b
Explanation: Consider y=\((log⁡2x)^{sin⁡3x}\)
Applying log on both sides, we get
log⁡y=\(log⁡(log⁡2x)^{sin⁡3x}\)
log⁡y=sin⁡3x log⁡(log⁡2x)
Differentiating with respect to x, we get
\(\frac{1}{y} \,\frac{dy}{dx}=log⁡(log⁡2x)\frac{d}{dx} (sin⁡3x)+sin⁡3x \frac{d}{dx} \,(log⁡(log⁡2x))\)
By using chain rule, we get
\(\frac{1}{y} \,\frac{dy}{dx}=log⁡(log⁡2x).3 \,cos⁡3x+sin⁡3x.\frac{1}{log⁡2x}.\frac{1}{2x}.2 \,(∵u.v=u’ \,v+uv’)\)
\(\frac{dy}{dx}\)=y(3 cos⁡3x log⁡(log⁡2x)+\(\frac{sin⁡3x}{x \,log⁡2x}\))
∴\(\frac{dy}{dx}\)=log⁡2xsin⁡3x \(\left (3 \,cos⁡3x \,log⁡(log⁡2x)+\frac{sin⁡3x}{x \,log⁡2x} \right )\)
advertisement

2. Differentiate 4xex with respect to x.
a) xex e-x (x log⁡x+1)
b) -4xex-1 ex (x log⁡x+1)
c) 4xex ex (x log⁡x+1)
d) 4xex-1 ex (x log⁡x+1)
View Answer

Answer: d
Explanation: Consider y=4xex
Applying log on both sides, we get
log⁡y=log⁡4xex
log⁡y=log⁡4+log⁡xex (∵log⁡ab=log⁡a+log⁡b)
Differentiating both sides with respect to x, we get
\(\frac{1}{y} \frac{dy}{dx}=0+\frac{d}{dx}(e^x \,log⁡x)(∵log⁡a^b=b \,log⁡a)\)
\(\frac{1}{y} \frac{dy}{dx}=\frac{d}{dx} \,(e^x) \,log⁡x+e^{x} \,\frac{d}{dx} \,(log⁡x)\)
\(\frac{dy}{dx}=y(e^x log⁡x+\frac{e^x}{x})\)
\(\frac{dy}{dx}=\frac{4x^{e^{x}}e^x \,(x log⁡x+1)}{x}=4x^{e^x-1} \,e^x \,(x log⁡x+1)\).

3. Differentiate 9tan⁡3x with respect to x.
a) 9tan⁡3x (3 log⁡9 sec2⁡x)
b) 9tan⁡3x (3 log⁡3 sec2⁡⁡x)
c) 9tan⁡3x (3 log⁡9 sec⁡x)
d) -9tan⁡3x (3 log⁡9 sec2⁡⁡x)
View Answer

Answer: a
Explanation: Consider y=9tan⁡3x
Applying log on both sides, we get
log⁡y=log⁡9tan⁡3x
Differentiating both sides with respect to x, we get
\(\frac{1}{y} \frac{dy}{dx}=\frac{d}{dx} \)(tan⁡3x.log⁡9)
\(\frac{1}{y} \frac{dy}{dx}=\frac{d}{dx} \,(tan⁡3x) \,log⁡9+\frac{d}{dx} \,(log⁡9).tan3x \,(∵ Using \,u.v=u’ \,v+uv’)\)
\(\frac{dy}{dx}\)=y(3 sec2⁡⁡x.log⁡9+0)
\(\frac{dy}{dx}\)=9tan⁡3x (3 log⁡9 sec2⁡x)
advertisement
advertisement

4. Differentiate (cos⁡3x)3x with respect to x.
a) (cos⁡3x)x (3 log⁡(cos⁡3x) – 9x tan⁡3x)
b) (cos⁡3x)3x (3 log⁡(cos⁡3x) + 9x tan⁡3x)
c) (cos⁡3x)3x (3 log⁡(cos⁡3x) – 9x tan⁡3x)
d) (cos⁡3x)3x (log⁡(cos⁡3x) + 9 tan⁡3x)
View Answer

Answer: c
Explanation: Consider y=(cos⁡3x)3x
Applying log on both sides, we get
log⁡y=log⁡(cos⁡3x)3x
log⁡y=3x log⁡(cos⁡3x)
Differentiating both sides with respect to x, we get
\(\frac{1}{y} \frac{dy}{dx}=\frac{d}{dx} (3x \,log⁡(cos⁡3x))\)
By using u.v=u’ v+uv’, we get
\(\frac{1}{y} \frac{dy}{dx}\)=\(\frac{d}{dx} \,(3x) \,log⁡(cos⁡3x)+\frac{d}{dx} \,(log⁡(cos⁡3x)).3x\)
\(\frac{dy}{dx}\)=y(3 log⁡(cos⁡3x) + \(\frac{1}{cos⁡3x} \,. \frac{d}{dx} \,(cos⁡3x).3x)\)
\(\frac{dy}{dx}\)=y(3 log⁡(cos⁡3x) + \(\frac{1}{cos⁡3x} \,. \,(-sin⁡3x).\frac{d}{dx}(3x).3x)\)
\(\frac{dy}{dx}\)=y(3 log⁡(cos⁡3x) + \(\frac{1}{cos⁡3x} \,. \,(-sin⁡3x).3.3x)\)
\(\frac{dy}{dx}\)=y(3 log⁡(cos⁡3x) – 9x tan⁡3x)
\(\frac{dy}{dx}\)=(cos⁡3x)3x (3 log⁡(cos⁡3x) – 9x tan⁡3x)

5. Differentiate 7x(2e2x) with respect to x.
a) 14e2x x(2e2x) (2 log⁡x+\(\frac{1}{x}\))
b) 14x(2e2x) (2 log⁡x+\(\frac{1}{x}\))
c) 14e2x x(2e2x) (2 log⁡x-\(\frac{1}{x}\))
d) 14e2x x(2e2x) (log⁡x-\(\frac{1}{x}\))
View Answer

Answer: a
Explanation: Consider y=7x(2e2x)
log⁡y=log⁡7x(2e2x)
log⁡y=log⁡7+log⁡x(2e2x)
log⁡y=log⁡7+2e2x log⁡x
Differentiating with respect to x on both sides, we get
\(\frac{1}{y} \frac{dy}{dx}\)=\(\frac{d}{dx}\) (log⁡7+2e2x log⁡x)
\(\frac{1}{y} \frac{dy}{dx}\)=0+\(\frac{d}{dx}\) (2e2x) log⁡x+\(\frac{d}{dx}\) (log⁡x)2e2x (using u.v=u’ v+uv’)
\(\frac{1}{y} \frac{dy}{dx}\)=2e2x.2.log⁡x+\(\frac{2e^{2x}}{x}\)
\(\frac{dy}{dx}\)=y\( \left (4e^{2x} \,log⁡x+\frac{2e^{2x}}{x}\right)\)
\(\frac{dy}{dx}\)=7x(2e2x) \( \left (4e^{2x} \,log⁡x+\frac{2e^{2x}}{x}\right)\)
\(\frac{dy}{dx}\)=14e2x x(2e2x) (2 log⁡x+\(\frac{1}{x}\))
advertisement

6. Differentiate \(e^{4x^5}.2x^{log⁡x^2}\) with respect to x.
a) \(e^{4x^5}.x^{log⁡x^2-1} (10x^5+log⁡2x^2)\)
b) \(4e^{4x^5}.x^{log⁡x^2-1} (10x^5+log⁡2x^2)\)
c) \(4e^{4x^5}.x^{log⁡x^2-1} (10x^5-log⁡2x^2)\)
d) \(x^{log⁡x^2 -1} (10x^4+log⁡2x^2)\)
View Answer

Answer: b
Explanation: Consider y=\(e^{4x^5}+2x^{log⁡x^2}\)
Applying log on both sides, we get
log⁡y=\(log⁡e^{4x^5} \,+ \,log⁡2x^{log⁡x^2}\)
log⁡y=\(4x^5+log⁡x^2 \,. \,log⁡2x\)
log⁡y=\(4x^5+2 \,log⁡x \,log⁡2x\)
Differentiating with respect to x, we get
\(\frac{1}{y} \frac{dy}{dx}\)=\(20x^4+2(\frac{d}{dx} \,(log⁡x) \,log⁡2x+\frac{d}{dx} \,(log⁡2x) \,log⁡x)\)
\(\frac{1}{y} \frac{dy}{dx}\)=\(20x^4+2\left (\frac{log⁡2x}{x}+\frac{1}{2x}.2.log⁡x\right )\)
\(\frac{1}{y} \frac{dy}{dx}\)=\(20x^4+\frac{2(log⁡2x+log⁡x)}{x}\)
\(\frac{1}{y} \frac{dy}{dx}\)=\(20x^4+\frac{2(log⁡2x^2)}{x}\)
\(\frac{dy}{dx}\)=\(y(20x^4+\frac{2(log⁡2x^2)}{x})\)
\(\frac{dy}{dx}\)=\(e^{4x^5}.2x^{log⁡x^2} (20x^4+\frac{2(log⁡2x^2)}{x})\)
\(\frac{dy}{dx}\)=\(4e^{4x^5}.x^{log⁡x^2 -1} (10x^5+log⁡2x^2)\)

7. Differentiate 2(tan⁡x)cot⁡x with respect to x.
a) 2 csc2⁡x.tan⁡xcot⁡x (1-log⁡(tan⁡x))
b) csc2⁡x.tan⁡xcot⁡x (1-log⁡(tan⁡x))
c) 2 csc2⁡x.tan⁡xcot⁡x (1+log⁡(tan⁡x))
d) 2tan⁡xcot⁡x (1-log⁡(tan⁡x))
View Answer

Answer: a
Explanation: Consider y=2(tan⁡x)cot⁡x
Applying log in both sides,
log⁡y=log⁡2(tan⁡x)cot⁡x
log⁡y=log⁡2+log⁡(tan⁡x)cot⁡x
log⁡y=log⁡2+cot⁡x log⁡(tan⁡x)
Differentiating both sides with respect to x, we get
\(\frac{1}{y} \frac{dy}{dx}=0+\frac{d}{dx} \,(cot⁡x) \,log⁡(tan⁡x)+cot⁡x \frac{d}{dx} \,(log⁡(tan⁡x))\)
\(\frac{1}{y} \frac{dy}{dx}=-csc^{2⁡}x.log⁡(tan⁡x)+cot⁡x.\frac{1}{tan⁡x}.sec^{2⁡}x\)
\(\frac{dy}{dx} = y\left(-csc^{2⁡x}.log⁡(tan⁡x)+\frac{(1+tan^{2⁡x})}{tan^{2⁡x}}\right)\)
\(\frac{dy}{dx}\)=2(tan⁡x)cot⁡x \(\left (-csc^{2⁡x} log⁡(tan⁡x)+cot^{2⁡x}+1 \right )\)
\(\frac{dy}{dx}\)=2(tan⁡x)cot⁡x \((-csc^{2⁡x} log⁡(tan⁡x)+csc^{2⁡x})\)
\(\frac{dy}{dx}\)=2(tan⁡x)cot⁡x (csc2⁡x (1-log⁡(tan⁡x))
∴\(\frac{dy}{dx}\)=2 csc2⁡x.tan⁡xcot⁡x (1-log⁡(tan⁡x))
advertisement

8. Differentiate (3 cos⁡x)x with respect to x.
a) (3 cos⁡x)x (log⁡(3 cos⁡x)+x tan⁡x)
b) (3 cos⁡x)x (log⁡(3 cos⁡x)+tan⁡x)
c) (cos⁡x)^x (log⁡(3 cos⁡x)-x tan⁡x)
d) (3 cos⁡x)x (log⁡(3 cos⁡x)-x tan⁡x)
View Answer

Answer: d
Explanation: Consider y=(3 cos⁡x)x
Applying log on both sides, we get
log⁡y=log⁡(3 cos⁡x)x
log⁡y=x log⁡(3 cos⁡x)
log⁡y=x(log⁡3+log⁡(cos⁡x))
Differentiating both sides with respect to x, we get
\(\frac{1}{y} \frac{dy}{dx} =\frac{d}{dx} (x log⁡3)+\frac{d}{dx} (x) log⁡(cos⁡x)+\frac{d}{dx}(log⁡(cos⁡x)).x\)
\(\frac{1}{y} \frac{dy}{dx}=log⁡3+log⁡(cos⁡x)+\frac{1}{cos⁡x}.-sin⁡x.x\)
\(\frac{1}{y} \frac{dy}{dx}\)=log⁡3+log⁡(cos⁡x)-x tan⁡x
\(\frac{dy}{dx}\)=y(log⁡(3 cos⁡x)-x tan⁡x)
\(\frac{dy}{dx}\)=(3 cos⁡x)x (log⁡(3 cos⁡x)-x tan⁡x)

9. Differentiate \(\sqrt{\frac{x+1}{3x-1}}\) with respect to x.
a) \(\frac{-2}{(3x-1)\sqrt{(3x-1)(x+1)}}\)
b) \(\frac{2}{(3x-1)\sqrt{(3x-1)(x+1)}}\)
c) \(\frac{1}{(3x-1)\sqrt{(3x-1)(x+1)}}\)
d) \(\frac{-2}{\sqrt{(3x-1)(x+1)}}\)
View Answer

Answer: a
Explanation: Consider y=\(\sqrt{\frac{x+1}{3x-1}}\)
Applying log to both sides, we get
log⁡y=log⁡\(\sqrt{\frac{x+1}{3x-1}}\)
log⁡y=\(\frac{1}{2} log⁡\left (\frac{x+1}{3x-1}\right )\)
log⁡y=\(\frac{1}{2}\) (log⁡(x+1)-log⁡(3x-1))
Differentiating with respect to x, we get
\(\frac{1}{y} \frac{dy}{dx}\)=\(\frac{1}{2}\left (\frac{d}{dx} (log⁡(x+1))-\frac{d}{dx} (log⁡(3x-1))\right )\)
\(\frac{1}{y} \frac{dy}{dx}\)=\(\frac{1}{2}\left (\frac{1}{x+1}-\frac{3}{3x-1}\right )\)
\(\frac{1}{y} \frac{dy}{dx}\)=\(\frac{1}{2}\left (\frac{3x-1-3x-3}{(x+1)(3x-1)})\right )\)
\(\frac{1}{y} \frac{dy}{dx}\)=\(\frac{1}{2}\left (\frac{-4}{(x+1)(3x-1)}\right )\)
\(\frac{dy}{dx}\)=\(\sqrt{\frac{x+1}{3x-1}} \left (\frac{-2}{(x+1)(3x-1)}\right )\)
\(\frac{dy}{dx}\)=\(\frac{-2}{(3x-1) \sqrt{(3x-1)(x+1)}}\)
advertisement

10. Differentiate x3ex with respect to x.
a) 3e3x (3 log⁡x+\(\frac{1}{x}\))
b) x3e3x.3e3x (3 log⁡x-\(\frac{1}{x}\))
c) x3e3x (3 log⁡x+\(\frac{1}{x}\))
d) x3e3x.3e3x (3 log⁡x+\(\frac{1}{x}\))
View Answer

Answer: d
Explanation: Consider y=x3e3x
Applying log on both sides, we get
log⁡y=3e3x log⁡x
Differentiating both sides with respect to x, we get
\(\frac{1}{y} \frac{dy}{dx} = \frac{d}{dx} (3e^{3x}) log⁡x+\frac{d}{dx} (log⁡x)3e^{3x}\)
\(\frac{1}{y} \frac{dy}{dx}\)=3e3x.3.log⁡x+\(\frac{1}{x}\) 3e3x
\(\frac{dy}{dx}\)=y(3e3x.3.log⁡x+\(\frac{1}{x}\) 3e3x)
\(\frac{dy}{dx}\)=x3e3x.3e3x (3 log⁡x+\(\frac{1}{x}\))

Sanfoundry Global Education & Learning Series – Mathematics – Class 12.

To practice all areas of Mathematics, here is complete set of 1000+ Multiple Choice Questions and Answers.

Participate in the Sanfoundry Certification contest to get free Certificate of Merit. Join our social networks below and stay updated with latest contests, videos, internships and jobs!

advertisement
advertisement
Manish Bhojasia - Founder & CTO at Sanfoundry
Manish Bhojasia, a technology veteran with 20+ years @ Cisco & Wipro, is Founder and CTO at Sanfoundry. He is Linux Kernel Developer & SAN Architect and is passionate about competency developments in these areas. He lives in Bangalore and delivers focused training sessions to IT professionals in Linux Kernel, Linux Debugging, Linux Device Drivers, Linux Networking, Linux Storage, Advanced C Programming, SAN Storage Technologies, SCSI Internals & Storage Protocols such as iSCSI & Fiber Channel. Stay connected with him @ LinkedIn | Youtube | Instagram | Facebook | Twitter